Programs for developing critical thinking skills in public education schools in Singapore and Australia and the possibility of benefiting from them in the Kingdom of Saudi Arabia: A comparative Study - Alharbi, Raneem Hamid (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify methods for developing critical thinking skills programs in public education schools in the Kingdom of Saudi Arabia in light of the experiences of Singapore and Australia, and the researcher followed the descriptive and comparative approach through George Periday's approach to comparative education, according to its steps: description, interpretation, Juxtaposition, and comparison The study sample consisted of documents, reports, and previous studies of the ministries of education of the countries of comparison and the Kingdom of Saudi Arabia. The study reached a set of results, the most important of which are: that there are similarities and differences in the methods of developing critical thinking programs between the Kingdom and the countries of study, and it recommended the need to develop mechanisms Developmental programs for critical thinking, and their use in the educational process, such as the interest in including books and courses on critical thinking strategies.
Keywords: Critical Thinking; Critical Thinking Programs; Thinking Skills